Problems Encountered in Day-To-Day Experience of Person Deprived of Liberty in Caloocan City Jail: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research was conducted to identity the problems encountered in the day-to-dayexperience of a person deprived of liberty in Caloocan City Jail. Questions were formulated toguide the study.On the basis of such findings, recommendations were established that the government shouldadd or build new prisons or jails to solve the problem of prison overcrowding. The governmentshould fortify the security in each cell by employing more personnel to control the violencehappening inside the prison. Prioritize city jails, especially in conducting medical missions, sothat prisoners will have an opportunity to check their condition. In the gathered data, theresearchers found that there are many problems inside the jail that PDLs encounter in theirdaily lives. This study revealed that PDL’s problem that was experienced inside the jail has ahuge impact on their safety and health- physical and mental. This study also revealed thatsome problems PDLs experience are caused by their co-prisoners or co-PDLs. Someproblems PDLs encountered are due to lacking of staff and government. This demonstratesthe importance of proposing measures to solve the problems and lessen the chance ofexperiencing worse or bigger problems. And the actions the government or authorities shouldbe taken. Through conducting this study, researchers have been able to see the mostcommon problem encountered by PDLs in terms of facility is inadequate bedding- the lack ofbedding types of equipment such as pillows, blankets, and bed sheets. And poor ventilation, inwhich PDLs are enabled to get fresh air. On the other hand, the majority of the respondentsagreed that the problem they most experience in terms of sanitation is their unhygienic livingconditions.
Keywords: Criminology